2022
DOI: 10.3390/agronomy12020407
|View full text |Cite
|
Sign up to set email alerts
|

Can Split Application of Slow-Release Fertilizer Improve Wheat Yield, Nitrogen Efficiency and Their Stability in Different Ecological Regions?

Abstract: Environmental conditions (precipitation, temperature and soil properties) differ greatly in different regions and have dual effects on the wheat growth and nutrient release of slow-release fertilizer (SRF). Conventional fertilization methods such as the multiple-split application of urea and the one-time application of SRF may have difficulty achieving a stable and high wheat yield and nitrogen (N) efficiency in various environments. Therefore, the exploration of a rational application strategy of SRF is neede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…The results align with the study by Yang et al (2021) because the loam test soil exhibits trends that correlate with their ndings. As a result of a single application of NS, the inorganic N in the soil was kept at high levels before combining, but it decreased signi cantly due to N de ciency in later growth stages (Ma et al, 2022).…”
Section: Economic Analysismentioning
confidence: 99%
“…The results align with the study by Yang et al (2021) because the loam test soil exhibits trends that correlate with their ndings. As a result of a single application of NS, the inorganic N in the soil was kept at high levels before combining, but it decreased signi cantly due to N de ciency in later growth stages (Ma et al, 2022).…”
Section: Economic Analysismentioning
confidence: 99%
“…In wheat production, fertilization and watering strategies are also often considered for quality improvement ( Li et al, 2018 , 2019b ; Yu et al, 2018a , 2021 ). As nitrogen (N) is one of the most important and essential elements for wheat, N fertilizer is usually the most efficient input for simultaneously increasing grain protein content and grain yield in wheat production ( Zebarth et al, 2007 ; Malik et al, 2013 ; Zhen et al, 2018 , 2020 ; Zhong et al, 2018 , 2020 ; Ding et al, 2020 ; Xia et al, 2020 ; Hermans et al, 2021 ; Landolfi et al, 2021 ; Lyu et al, 2021 ; Dong et al, 2022 ; Liu et al, 2022 ; Ma et al, 2022 ). Kichey et al (2007) demonstrated that 50–95% of nitrogen in mature grains is derived from the remobilization of nitrogen stored in the tissues before anthesis.…”
Section: Manipulation Of Fertilization and Watering Regimesmentioning
confidence: 99%
“…In the research of field crops, N leaching usually means the process of water-soluble nitrate (NO 3 − -N) in soil migrates down to the root active layer, entering the groundwater under the influence of heavy rainfall or irrigation [25]. In addition, N leaching also refers to a difference between the amount of total N inputs and N outputs and the N change in the soil profile.…”
Section: N Leachingmentioning
confidence: 99%